ASSOCIATION OF ADIPONECTIN WITH TOTAL LEUKOCYTE COUNT IN PATIENTS OF CORONARY ARTERY DISEASE - Sadaf Durrani,; Sobia Ali,; Ubaid ur Rahman,; Mehnaz Khattak,; Naheed Khattak,; Romana Irshad,; Mudassir Ahmad Khan, (Journal of Ayub Medical College Abbottabad, 2022)
Background: Hypoadiponectinemia and raised total leukocyte count have been associated with coronary artery disease. The aim of this study was to investigate association of serum adiponectin levels with total leukocyte count in patients of coronary artery disease belonging to Khyber Pakhtunkhwa. Methods: This cross-sectional/analytical study consisted of two groups. Group A contained 100 patients of coronary artery disease while group B contained 100 healthy controls. Consent of the study subjects was obtained, their history was recorded and fasting blood samples were analyzed for serum adiponectin level, total leukocyte count (TLC), serum lipid profile which included serum total cholesterol (T-C), triglyceride level (TG), high-density lipoprotein cholesterol (HDL-C) and low-density lipoprotein cholesterol (LDL-C). Adiponectin level was determined with ELIZA method, TLC was estimated on automated hematology analyzer and lipid profile was determined using enzymatic colorimetric method. SPSS version 21 was used to analyze the data. Results: Subjects with coronary artery disease when compared to healthy subjects showed significantly high level of total leukocyte count (9.26±1.488 vs. 6.37±4.052) and low level of serum adiponectin (4.3±0.80 vs. 9.6±3.69). Moreover, serum lipid profile showed low HDL-C (30.04±9.1 vs. 43.64±7.3) and raised triglyceride (220.1±67.7 vs. 181.86±41.4), total cholesterol (229.3±37.01 vs. 189.4±32.7), and LDL-C (153.78±38.53 vs. 109.16±33.91) levels. Significant negative association of adiponectin with TLC (r -0.826 with p<0.01) was observed in the study subjects. Conclusion: We observed elevated level of total leukocyte count and reduced level of adiponectin in subjects with coronary artery disease. Moreover, hypoadiponectinemia correlated negatively with TLC levels.